A new species and a new record of Mallocybe (Inocybaceae, Agaricales) from Pakistan uncovered by integrated morphology and phylogeny - Kiran, Munazza; Sana; Sattar, Ammara; Khalid, Abdul Nasir (Phytotaxa, 2025)
Taxonomic investigations of the family Inocybaceae were conducted in Pakistan during the monsoon seasons of 2017 to 2022. Morphological examination and phylogenetic analyses based on nrITS and nrLSU sequences of the collected specimens led to the discovery of a new species, Mallocybe luteoaurantiaca, and the first geographic record of M. crassivelata from Pakistan. Mallocybe luteoaurantiaca is characterized by a hemispherical to spherical, broadly parabolic and bright brown to yellow-orange pileus, adnate to sinuate and pale yellow to yellow-orange lamellae, a concolorous stipe with the pileus, oblong to ellipsoid basidiospores, and utriform to narrowly utriform cheilocystidia. Phylogenetic inference positioned M. luteoaurantiaca as a distinct lineage, forming a well-supported sister clade to M. fuscomarginata. Another Pakistani collection, identified as M. crassivelata, forms a strongly supported sister clade with the holotype of M. crassivelata and shows clear morphological distinctions from it, such as variation in pileus margin, lamellar attachment and coloration, stipe pigmentation, and spore and cystidial characteristics. However, as its nrITS+nrLSU region differs from that of the holotype of M. crassivelata by only three nucleotide substitutions, it is here interpreted as a new geographical record of M. crassivelata rather than a novel species. Descriptions, illustrations, phylogenetic analysis results, and comparisons with closely related taxa are provided for the studied species.